KARAKTERISTIK AERODINAMIS DUA SILINDER TERIRIS TYPE 1 YANG TERSUSUN SIDE BY SIDE PADA BILANGAN REYNOLDS SUBKRITIS - Indra Herlamba Siregar; Abdul Muis (Mesin, 2007)
Experimental studies of aerodynamics characteristics of two cylinders type I in side by side configuration at sub-critical Reynolds number were carried out at open circuit of subsonic wind tunnel. Gap of side by side configuration T/D was varied from 1.1 to 4 and sliced angle both of frontage an behind cylinder at 45°, 53° and 65°. Total drag reduce since gap of cylinders increase for sliced angle 45° and 53° but increase for sliced angle 65°. Bias flow phenomenon showed at close and moderate gap of cylinders tend to symmetries at width gap. Visualization have done with smoke method to get more information about characteristics of two cylinders type I in side by side configuration